Hukum Pencemaran Lingkungan terhadap Limbah Industri sebagai Ancaman Bencana Ekologis: Studi Kasus Limbah Industri di IMIP Morowali - Rayi Kharisma Rajib; Vivi Dyelsa; Olivia Rahma Oktaviani (INDO PUBLISHING, 2026)
Environmental pollution caused by industrial waste is a serious problem with the potential to trigger ecological disasters, particularly in large industrial zones such as the Indonesia Morowali Industrial Park (IMIP). This study aims to analyze legal regulations regarding environmental pollution, examine the liability of polluters, and evaluate the effectiveness of environmental law enforcement in Indonesia using a normative legal approach. The results of the study indicate that Indonesia has a fairly comprehensive legal framework, particularly through the Law on Environmental Protection and Management. However, implementation and enforcement still face challenges, such as weak oversight. The legal liability of polluters covers administrative, civil, and criminal aspects, but has not been optimally enforced. Therefore, strengthened oversight, consistent law enforcement, and synergy among stakeholders are required.